(untitled) (Acta Scientiarum. Animal Sciences, 2017)
The objective of this study was to compare methods for estimative of body composition of goats based on tritiated water space technique (TOH), specific gravity (SG) of carcass and 9-11th ribs. Ten Toggenburg x Alpine intact male goat kids, from 5.3±0.4 to 25.9±1.3 kg of body weight (BW), were used to estimate body composition by: 1) direct method, 2) TOH method, 3) SG of the carcass and 4) SG of the 9-11th whole ribs. In addition, update linear equations for predicting body composition were developed using data from direct method. The TOH space overestimated water body composition on average 31%. The SG of the carcass and 9-11th ribs underestimated water empty body composition (%) on average 21 and 12%, respectively. In spite of its overestimate, the determination of TOH space can be used as a reliable field technique to study relative changes in body composition of growing goats. Specific gravity is practicable in most circumstances and does not require expensive equipment. However, the SG of the carcass and 9-11th ribs has not a valid equation to predict body composition of growing goats.